Lifestyle of Young Men Who Have Sex with Men Living with HIV: A Qualitative Descriptive Study - Rueanrudipirom , Kheamnareenee; Fongkaew, Warunee; Viseskul , Nongkran; Fongkaew, Kangwan (Pacific Rim International Journal of Nursing Research, 2021)
There has been an increase of HIV infection among young men who have sex with men worldwide, including in Thailand. They need to take care of themselves, to balance their health and to avoid HIV transmission to others. Existing studies show that young men who have sex with men living with HIV still engage in risky behaviors which can lead to health problems. Only a few research studies have been performed to explain how the lifestyles of such men influence the maintenance of their health and more studies are needed to encourage better health outcomes for them. This qualitative descriptive study explored the lifestyles of 20 young men aged 15 – 24 years old who had sex with men living with HIV in northern Thailand from May 2018 to May 2019. The data were collected via in-depth interviews and analyzed using thematic analysis. The findings were categorized into three themes: 1) attempting to have a ‘normal’ life: comprised of learning to live normally, concealing HIV status, and having hope to live a long life, 2) striving to fulfill sexual lives included masturbation to release sexual desire and having oral sex, and 3) restyling healthy behaviors: by reducing risk behaviors, seeking ways to cope with stress, managing to take antiretroviral drugs as daily life, and using condoms for prevention. The findings of this study help nurses to understand the lifestyle of young men who have sex with men living with HIV, which can be used to develop programs/strategies to promote healthy lifestyles and well-being.